Strategi Vietnam Mendorong Peningkatan Climate Foreign Direct Investment (FDI) dalam Transisi Energi Terbarukan Periode 2014-2024 - Diki Angger Arianto (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
Vietnam, highly vulnerable to climate change, has successfully secured the largest climate finance in Southeast Asia, making it a compelling case study for attracting foreign direct investment (FDI) in renewable energy transition. This qualitative study, analyzing secondary data from 2014 to 2024 and framed by Institutional Theory and the Climate FDI concept, investigates the strategies behind this achievement. The findings reveal that Vietnam's strategy hinges on a synergy of formal and informal institutions. Formally, the government acts as a primary catalyst through policies like the Power Development Plan VIII (PDP8) and Feed in Tariff (FiT), which provide regulatory certainty, fiscal incentives, and a net-zero 2050 commitment to reduce investor risk. This is supported by state budget allocations for grid infrastructure, skilled workforce training, and integrated land use policies. Informally, shifting social norms driving clean energy demand, trust based business collaborations, and an innovation culture supported by academics and NGOs play a crucial role. Together, this combination creates a legitimized, efficient, and responsive investment environment that effectively attracts green FDI to overcome the challenges of its energy transition
Reaploud Repository February_Hasyim
Keywords: Climate Change; Energy Transition; Climate FDI; Institutional Theory; Vietnam.